Diversity of bats at two contrasting elevations in a protected dipterocarp forest in Sarawak, Borneo - Mohd-Azlan, J.; Siti Hasmah, Taha; Laman, Charlie J.; M.T, Abdullah (Northern Territory Government, 2008)
We present an assessment of the diversity of Bornean bats at two contrasting elevations (119 m and 787 m) in Kubah National Park surveyed between August and December 2006. Three hundred and eighty-two individuals of bats from 26 species representing six families were recorded using 20 mist nets and three harp traps. The most commonly caught bat was Hipposideros cervinus (Gould, 1863) (n = 168) followed by Penthetor lucasi (Dobson, 1880) (n =55), and they were also recorded specimen of Pipistrellus cuprosus Hill and Francis, 1984 for Sarawak. Analysis of daily cumulative capture rates indicated that further effort at these sites may not yield additional species if sampling techniques and locations are maintained. Species diversity index of Megachiroptera was higher at high elevations (H’ = 0.567 versus H’ = 0.466)whereas the species diversity index of Microchiroptera was greatest at low elevations (H’= 0.905 vs H’ = 1.225).